Anterior hypopituitarism in a patient with amyloidosis secondary to Crohn’s disease: a case report - Verbeke, Natacha (J Med Case Rep, 2018)
BACKGROUND: Amyloid infiltration of endocrine glands has been reported, mostly in the thyroid, pancreas, adrenals, and testes, but affected patients do not frequently exhibit overt endocrine insufficiency. Here we report the case of a patient with complete anterior hypopituitarism probably due to a known systemic amyloidosis. CASE PRESENTATION: Our male Caucasian patient was diagnosed with Crohn’s disease at the age of 22 years. At the age of 37, he developed secondary renal amyloidosis, which resulted in end-stage renal failure. He received a living-donor kidney transplant at the age of 57, without initial complication. Two months later, he developed extreme fatigue, weight loss, and dyspnea. A hormonal evaluation demonstrated complete anterior pituitary insufficiency. A pituitary magnetic resonance imaging was performed and showed a diffusely hypointense anterior gland on both T1-weighted and T2-weighted images with reduced gadolinium enhancement, highly suggestive of amyloid infiltration of the pituitary. Treatment was initiated with levothyroxine, orally administered hydrocortisone, and testosterone enanthate, rapidly allowing progressive marked clinical improvement and nearly complete resolution of symptoms. CONCLUSIONS: Pituitary amyloid infiltration should be considered in patients with a known systemic amyloidosis who develop symptoms of hypopituitarism and magnetic resonance imaging features compatible with protein deposits.